A case study of the successful implementation of workload control: A practitioner-led approach. Issue 2 (2nd March 2015) - Silva, Cristóvão; Stevenson, Mark; Thurer, Matthias
Abstract : Purpose: – Workload control (WLC) is a Production Planning and Control concept of particular relevance to small and medium sized make-to-order companies. Despite the simplicity of its core principles, few successful implementations have been reported, and both understanding and awareness of the concept amongst practitioners is limited. The authors describe a rare successful implementation of WLC in which elements of the concept were embedded in a company to support both customer enquiry management and order release. The purpose of this paper is to focus on the implementation process itself rather than the impact on performance. Design/methodology/approach: – A particularly novel aspect of the case is that the implementation was practitioner (rather than researcher) led. A manager chose to read up on and implement the concept, creating a strong in-house commitment to the initiative. The researchers played a facilitating role, e.g. intervening where necessary to answer questions and advise. A factory visit/tour and interview were also conducted post implementation to reflect on the process. Findings: – The authors identify the elements of WLC implemented by the practitioner and how they were refined to meet company requirements, with implications for improving the alignment between theory and practice. The paper also informs the implementation process, for example, by highlighting the importance of managerial championing for implementation success and how WLC can be implemented based on a reasonably simple Excel© spreadsheet. Research limitations/implications: – More empirical evidence is required to assess the generality of some of the adaptations made by the practitioner; and to collect longitudinal quantitative evidence on the performance of WLC over time. Simulations could also be conducted to confirm the effectiveness of adaptations observed in the study. Practical implications: – The case has implications for the process of implementing WLC and may provoke a rethink in terms of the range of companies for which the concept is thought to be appropriate – the case described is of a larger, higher volume company than most previous WLC implementations. Originality/value: – A rare case of a successful implementation of WLC at both the customer enquiry management and order release levels; the only practitioner-led implementation of WLC reported in the literature to date.